FUNCTIONAL BLOOD CIRCULATION VALUES IN PATIENTS WITH IMPLANTED PACEMAKERS AND CARDIAC RESYNCHRONIZATION THERAPY AFTER YEAR OF PERMANENT PACING IN DIFFERENT QRS COMPLEX DURATION CLASSES - Shanina, I. V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
Functional blood circulation values were prospectively investigated in 100 patients (46 – women, 54 – men) with permanent pacemakers and in 29 patients (10 – women, 19 – men) – with cardiac resynchronization therapy (CRT) with mean age 69 ± 7 years in different observation stages taking into account QRS complex duration classes (class 1 – under 120 ms (normal), 2 – 120-149 ms (long) and 3 – more than 150 ms (significantly elongated)). Medication support was included beta-blockers; amiodarone; renin-angiotensin-aldosterone system inhibitors: angiotensin converting enzyme and angiotensin II inhibitors; antithrombotic agents; oral anticoagulants; statins and diuretics. Ventricular rate of spontaneous and stimulated rhythm; systolic and diastolic blood pressure; ejection fraction, end-diastolic and end-systolic volumes of the left ventricle; interventricular septum thickness and left ventricular posterior wall, right atria and ventricle sizes were evaluated. The results showed that QRS complex widening associated with greater deviation of functional blood circulation values from physiological norms. Permanent pacing with medical support had no significant impact on the functional blood circulation values, and CRT contributed reverse remodeling higher in class 3 of QRS complex duration. Also it was concluded that there is a necessity of medical support improvement.